Penerapan Model Pembelajaran Berlandaskan Pengembangan Kepribadian pada Program Studi Pendidikan Matematika - Agoestanto, Arief (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2010)
This classroom action research applied personality based learning which increase students' condition as subject of progressing their personality. The aims of the research were involving personality based learning model for students as mathematics teacher candidate, increasing students' affection, study result based personality, dynamics of students' activities and students' learning process were followed multi directions interactions among students. The main finding of this study, the average of first cycle test was 50,2 and the post-test was 57, difference between them was 6,8. The average of activities and competence performance during first cycle was 6,8 this value was more than success standard i.e. 6,5. The habits of study based personality was not enough planted in themselves, but this was decreased in next cycles. The average of teaching lecturer's performance during first cycle was good enough i.e. 7,1 so that was more thansuccess indicator i.e. 6,5. The average of second cycle was good enough i.e. 72,94 and the difference between them was 5,02 it was more than 5 so standard of success was attained. The average of individual score in team work was 66,67 it was more than minimum success indicator i.e. 6,5. The average of teaching lecturer's performance in second cycle was 8,07 more than first one i.e. 7,33 maybe caused the lecturer was more familiar with this method.Keywords: personality based learning, mathematics teacher candidate